Comparative SEM/EDS analysis of gunshot residue from non-toxic and traditional ammunitions employed by Dubai police - Askar, Asma M.; Alblooshi, Roudha A.; Alobeidli, Hamda A.; Alremeithi, Rashed H.; Shah, Iltaf (Frontiers in Chemistry, 2025)
Analysis and identification of gunshot residue (GSR) are considered critical forensic evidence in shooting incident investigations. This study comparatively analyzed gunshot residue from Fiocchi non-toxic ammunition (NTA), ADCOM, and NATO ammunitions, all commonly utilized by Dubai Police, using Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM/EDS) following the American Society for Testing and Materials (ASTM) E1588-20 standards. The elemental compositions of ammunition components, including cartridge cases, bullets, gunpowder, and primers, were thoroughly characterized. Primer residue revealed significant elemental differences, with Fiocchi NTA ammunition unexpectedly containing detectable lead particles, although at lower levels compared to ADCOM and NATO ammunition. Across all ammunition types, GSR particles predominantly measured below 3 μm, effectively differentiating them from common environmental contaminants. GSR particle deposition was consistently higher on shooters’ dominant right hands due to firearm mechanics and hand dominance. Particle counts generally decreased over time post-discharge but were influenced significantly by shooter activities rather than elapsed time alone. Notably, limitations within the ASTM E1588-20 classification scheme resulted in no identifiable Heavy-Metal-Free (HMF) GSR particles for Fiocchi NTA, emphasizing the need for updated and expanded classification criteria. Future research is recommended to enhance forensic methods and classification frameworks to accommodate evolving ammunition formulations.